Study on method of core collection construction for sensory quality traits of summer-planted vegetable soybean - HAN Li-de; HU Jin; XU Hai-ming; QIU Jia-xun; HUANG Zheng-lai (浙江大学学报. 农业与生命科学版)
A method of core collection construction for sensory quality traits of summer-planted vegetable soybean was investigated. A core collection, consisting of 36 summer-planted vegetable soybeans, was established by hierarchical cluster method with seven sensory quality traits (100-pod fresh weight, 100-seed fresh weight, seed number per pod, pod length, pod width, pod thickness, soluble sugar content) from 154 primary core accessions of vegetable soybean in the main production regions of China. Five parameters, namely, mean, range, variance, coefficient of variation and phenotypic correlation, were used to validate representative of the core collection. The result showed that the core collection for sensory quality traits well retained the genetic diversity and genetic complexity of the primary core accessions. The core collection for special traits may serve as an supplementary method for selecting excellent accession in quality breeding.